2016
DOI: 10.2215/cjn.12051115
|View full text |Cite
|
Sign up to set email alerts
|

Association of Urinary Biomarkers of Inflammation, Injury, and Fibrosis with Renal Function Decline: The ACCORD Trial

Abstract: Background and objectives Current measures for predicting renal functional decline in patients with type 2 diabetes with preserved renal function are unsatisfactory, and multiple markers assessing various biologic axes may improve prediction. We examined the association of four biomarker-to-creatinine ratio levels (monocyte chemotactic protein-1, IL-18, kidney injury molecule-1, and YKL-40) with renal outcome.Design, setting, participants, & measurements We used a nested case-control design in the Action to Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 40 publications
5
79
0
1
Order By: Relevance
“…This study found that higher donor urinary YKL-40 concentrations were associated with reduced risk of delayed graft function, suggesting that YKL-40 may positively impact the response to acute tubular injury [39]. In the ambulatory setting, a nested case-control study within the Action to Control Cardiovascular Risk in Diabetes trial found no association between urinary YKL-40 and kidney function decline during follow-up [40]. Our study builds upon the relatively sparse literature on urinary YKL-40 by demonstrating novel associations with mortality risk among persons with CKD.…”
Section: Discussionmentioning
confidence: 76%
“…This study found that higher donor urinary YKL-40 concentrations were associated with reduced risk of delayed graft function, suggesting that YKL-40 may positively impact the response to acute tubular injury [39]. In the ambulatory setting, a nested case-control study within the Action to Control Cardiovascular Risk in Diabetes trial found no association between urinary YKL-40 and kidney function decline during follow-up [40]. Our study builds upon the relatively sparse literature on urinary YKL-40 by demonstrating novel associations with mortality risk among persons with CKD.…”
Section: Discussionmentioning
confidence: 76%
“…5 With regard to the kidney, it has been shown that serum and urinary TFF3 significantly increase in patients with chronic kidney disease (CKD). [6][7][8] However, it is unclear whether the renal TFF3 expression is localized in the tubular epithelial cells, and whether it increases in the association with the tubulointerstitial injury in patients with CKD. No previous study has analyzed the mRNA expression in patients with CKD such as glomerulonephritis.…”
Section: Methodsmentioning
confidence: 99%
“…The TFF3 expression increases in various organs as the consequence of tissue damage such as inflammation or fibrosis . With regard to the kidney, it has been shown that serum and urinary TFF3 significantly increase in patients with chronic kidney disease (CKD) . However, it is unclear whether the renal TFF3 expression is localized in the tubular epithelial cells, and whether it increases in the association with the tubulointerstitial injury in patients with CKD.…”
mentioning
confidence: 99%
“…(12) Higher urine concentrations have been associated with greater fibrosis in diabetic nephropathy and with disease progression. (13) PINP and PIIINP are cleaved from type 1 and type 3 collagen fibrils during collagen deposition, which is an important step in fibrogenesis. (14) Urine PIIINP is the N-terminal fragment of type III collagen and is released during newly deposited collagen type III and is correlated with interstitial fibrosis (11) and kidney function decline(15) in patients with CKD of different etiologies (16) and in KTRs.…”
Section: Introductionmentioning
confidence: 99%